Assessing ecological sensitivity and economic potentials and regulation zoning of the riverfront development along the Yangtze River, China. (1st April 2021) - Duan, Xuejun; Zou, Hui; Wang, Lei; Chen, Weixiao; Min, Min
Abstract: The waterfront along great rivers, located in water-land and human-nature interaction zone, is a type of rare resource, which is critical for urban and industrial development and eco-environmental protection. The development and protection of riverfronts is one of the key components of sustainable watershed development. Waterfront development control, followed by regulation zoning that is based on different socio-economic and iconological functions, is regarded as one of the most important governance instruments for sustainable riverfront management. Based on the natural and socioeconomic attributes, we constructed a theoretical framework and integrated index system to evaluate the ecological sensitivity, development potential, and current development patterns of riverfront resources. The evaluation is further used as evidence for riverfront use zoning and future development governance through a case study in the Yangtze riverfront in China. The results show that more than 40% of the riverfront along the Yangtze River has high ecological sensitivity to economic development. The lengths of the development-prohibited, development-restricted, and development-optimized riverfront accounted for 70.0%, 6.5%, and 23.5% of the total evaluated Yangtze riverfront, respectively. Based on the assessment and field research, several problems were observed, such as the misuse of deep-water riverfront, conflicts between drinking water sources and heavy industrial development, and waterfront development in nature preservation areas. The riverfront zoning results can be used to support future riverfront development regulation and use optimization. Finally, we inferred some policy suggestions for future riverfront governance. Graphical abstract: The theoretical framework and integrated index system were developed to evaluate the ecological sensitivity, development potentials, and current development patterns of riverfront resources. The Yangtze Riverfront in China was examined. The lengths of the development-prohibited, development-restricted, and development-optimized riverfront accounted for 70.0%, 6.5%, and 23.5% of the total evaluated length, respectively. The zoning results can be used to support future riverfront development regulation and use optimization. Image 1 Highlights: Riverfront is conceptualized as resource from ecological and economic values. Yangtze Riverfront ecological sensitivity and development potentials were assessed. About 50% of the Yangtze riverfront has high or medium ecological sensitivity. Spatial mismatch problems of riverfront development were identified. Regulation zones were proposed for future riverfront development and governance.